THE INFLUENCE OF SCIENCE LEARNING INTRODUCING PLANT PARTS ON THE COGNITIVE DEVELOPMENT OF EARLY CHILDREN IN TK IT NADAASHOBAH - Titien Ruswanti; Ruqoyyah Fitri (International Journal of Teaching and Learning, 2024)
This study aims to examine the impact of nature-based science learning on the cognitive development of early childhood students at TK IT Nada Ashobah Wiyung Surabaya. The research method used is a quasi-experimental design with a one- group pretest-posttest design. The population in this study consists of all group B children at TK IT Nada Ashobah, totaling 15 children. The sampling technique used is saturated sampling. The sample consists of 15 group B children. The results show a significant improvement in children's understanding of plant parts after the treatment. The pretest indicated that most children were in the "Starting to Develop" category, while the posttest showed an increase, with the majority of children in the "Developing Very Well" category. The Wilcoxon test showed an Asymp (2-tailed) value of 0.001, indicating that nature-based science learning has a significant impact on children's cognitive development. The study concludes that the nature-based learning approach is effective in enhancing children's understanding and interest in science and recommends integrating this method into the early childhood education curriculum.